Musa fiber-reinforced PLA biocomposites and their mechanical properties - Enríquez-Medrano, Francisco Javier; Saade-Caballero, Hened; Mendoza-Carrizales, Ricardo; Medrano-Macías, Julia; Díaz Elizondo, José Alejandro (Revista Mexicana de Ciencias Agrícolas, 2025)
This study analyzed polylactic acid biocomposites reinforced with banana (Musa) fiber, evaluating its effect on mechanical properties before and after accelerated aging. Analyses (FTIR, XRD, TGA) confirmed that the fiber contains hemicellulose, cellulose, and lignin, with a higher cellulose fraction due to its high crystallinity. Before aging, tensile strength and tensile modulus did not show a significant improvement with increasing fiber content, although impact strength and hardness did improve slightly. Nevertheless, elongation at break decreased. After 240 h of exposure in the UV chamber, the mechanical properties of the biocomposites degraded, with a reduction in tensile strength and modulus and an increase in elongation at break. Despite this, the reinforced biocomposites showed better mechanical properties than pure PLA after aging.
Keywords: composite material; Musa fiber; polylactic acid